2015
DOI: 10.4274/jcrpe.1745
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing the Psychosocial Aspects of Type 1 Diabetes in Adolescents

Abstract: Objective:Considering the ever increasing population of diabetic adolescents and the association of the disease with psychosocial problems throughout its course, depression and/or anxiety and social support from parents are issues of special concern in these patients. The study aimed to identify the depression and anxiety state of diabetic adolescents and its impact on the management of diabetes mellitus (DM).Methods:295 adolescents with type 1 DM and their parents attended our study. Psychological distress wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 26 publications
3
19
1
3
Order By: Relevance
“…In the beginning, they often feel grief and anxiety and experience feelings of loneliness and social isolation (Cavusoglu, 2008b). Similar to these conditions, previous studies have found problems such as depression, anxiety, behavioral disorders, and eating problems in adolescents with T1DM (Adal et al, 2015;Schaaijk, Odink, Ultee, & Baar, 2011;Wisting, Frøisland, Skrivarhaug, Dahl-Jørgensen, & Rø, 2013). In our study, the characteristics of going through adolescence and having a chronic disease were related to high social anxiety levels in adolescents with T1DM.…”
Section: Comparison Of Sas-a Scores Of Adolescents With T1dm and Healsupporting
confidence: 79%
See 1 more Smart Citation
“…In the beginning, they often feel grief and anxiety and experience feelings of loneliness and social isolation (Cavusoglu, 2008b). Similar to these conditions, previous studies have found problems such as depression, anxiety, behavioral disorders, and eating problems in adolescents with T1DM (Adal et al, 2015;Schaaijk, Odink, Ultee, & Baar, 2011;Wisting, Frøisland, Skrivarhaug, Dahl-Jørgensen, & Rø, 2013). In our study, the characteristics of going through adolescence and having a chronic disease were related to high social anxiety levels in adolescents with T1DM.…”
Section: Comparison Of Sas-a Scores Of Adolescents With T1dm and Healsupporting
confidence: 79%
“…Similar to these conditions, previous studies have found problems such as depression, anxiety, behavioral disorders, and eating problems in adolescents with T1DM(Adal et al, 2015;Schaaijk, Odink, Ultee, & Baar, 2011;Wisting, Frøisland, Skrivarhaug, Dahl-Jørgensen, & Rø, 2013). Similar to these conditions, previous studies have found problems such as depression, anxiety, behavioral disorders, and eating problems in adolescents with T1DM(Adal et al, 2015;Schaaijk, Odink, Ultee, & Baar, 2011;Wisting, Frøisland, Skrivarhaug, Dahl-Jørgensen, & Rø, 2013).…”
supporting
confidence: 54%
“…An important distinction to recognize in the extant literature is studies that assess symptoms of anxiety through commonly administered questionnaires (e.g., Multidimensional Scale for Anxiety in Children; MASC [3], Screen for Anxiety Related Disorders; SCARED [4]) and those that classify participants as meeting the diagnostic criteria for a particular anxiety disorder through the use of semi-structured questionnaires (e.g., Kiddie Schedule for Affective Disorders and Schizophrenia [5]). In addition, the anxiety literature distinguishes between state and trait anxiety with the former occurring when there is a temporary emotional reaction involving worry and fear in response to a perceived threat and the latter being a more stable personality characteristic comprised of heightened worry and fear [6][7][8].…”
Section: Introductionmentioning
confidence: 98%
“…In their study of 295 adolescents with type 1 diabetes, Adal et al, [40] found a significant correlation with depression and anxiety with a reported depression rate of 12.9%. A number of other authors have also found these correlations of psychiatric symptoms with type 1 diabetes including the issue of psychomotor agitation, sleep difficulty, and eating disorders [34,[41][42][43][44].…”
Section: Type 1 and Type 2 Diabetesmentioning
confidence: 99%